2005
DOI: 10.1021/ja054708v
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Anomeric Interpretation of the “High-Energy” N−P Bond inN-Methyl-N‘-phosphorylguanidine:  Importance of Reinforcing Stereoelectronic Effects in “High-Energy” Phosphoester Bonds

Abstract: Electronic structure calculations have been performed on a model N-phosphorylguanidine, or phosphagen, to understand the stereoelectronic factors contributing to the lability of the "high-energy" N-P bond. The lability of the N-P bond is central to the physiological role of phosphagens involving phosphoryl transfer reactions important in cellular energy buffering and metabolism. Eight protonated forms of N-methyl-N'-phosphorylguanidine have been energy minimized at levels of theory ranging up to B3LYP/6-311++G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 78 publications
2
29
0
Order By: Relevance
“…The G°'s for hydrolysis of ATP and phosphocreatine are ~ -7.3 kcal/mol and ~ -10.3 kcal/mol, respectively, but under physiological conditions the differences are probably less significant [19]. It has been argued previously that the large negative free energy of hydrolysis of the phosphagens is due to difference in stabilities of + P-O versus + P-N bonds [20], which has led to the use of the term "high energy bonds".…”
Section: Thermodynamic Considerationsmentioning
confidence: 96%
See 4 more Smart Citations
“…The G°'s for hydrolysis of ATP and phosphocreatine are ~ -7.3 kcal/mol and ~ -10.3 kcal/mol, respectively, but under physiological conditions the differences are probably less significant [19]. It has been argued previously that the large negative free energy of hydrolysis of the phosphagens is due to difference in stabilities of + P-O versus + P-N bonds [20], which has led to the use of the term "high energy bonds".…”
Section: Thermodynamic Considerationsmentioning
confidence: 96%
“…Recent high level calculations have shown that in phosphoguanidines the guanidinium group dominates in the competition for the central nitrogen's lone pair of electrons and delocalisation onto the phosphoryl group is negligible (Fig. 14), and therefore opposing resonance cannot explain the large negative free energy of hydrolysis of the phosphagens [19]. Fig.…”
Section: Thermodynamic Considerationsmentioning
confidence: 99%
See 3 more Smart Citations